2017
DOI: 10.1021/acsomega.7b01800
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Loaded Supramolecular Gels Prepared in a Microfluidic Platform: Distinctive Rheology and Delivery through Controlled Far-from-Equilibrium Mixing

Abstract: It is shown here that controlled mixing of a gelator, drug, solvent, and antisolvent in a microfluidic channel leads to faster setting gels and more robust materials with longer release profiles than the physical gels of the same composition obtained using random mixing in solution. The system is similar to a related gelator system we had studied previously, but we were unable to apply the same gelling procedure because of the instability of the colloid caused by the small structural modification (length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In vitro drug release experiments were performed using Franz-type cells to evaluate the ability of the hydrogel to release the drug according to previously reported methodologies [ 19 ]. Figure 4 shows the cumulative amount of ketorolac released from the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro drug release experiments were performed using Franz-type cells to evaluate the ability of the hydrogel to release the drug according to previously reported methodologies [ 19 ]. Figure 4 shows the cumulative amount of ketorolac released from the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…26 The reorganization of the fibres in certain solvent conditions is facilitated here as a result of similar effects, where the movement of the traveller is accompanied by path change. The possibilities of changing the supramolecular fibre nature through controlled mixing in these systems 11,27 and others opens a myriad of possibilities to modulate the dynamic nature of the systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the degradation studies (Figure 3B), PF-NLCs-F127 hydrogel showed values of 1 h for weight loss corresponding to the gradual diffusion of the components of the hydrogel into the medium, indicating that the formulation could be successfully degraded when immersed in the biological medium. The mechanical properties of the gel are also affected by the incorporation of a drug [31]. The high porosity 95.76 ± 0.1%, as well as the hydrophilic behaviour of the fibres, is ideal from a drug delivery point of view, as with these characteristics it could permit the incorporation of solvent, and it explains the high and fast swelling observed, which reached a value of 100% after 7 min.…”
Section: Discussionmentioning
confidence: 99%